Meiotic Centromere Coupling and Pairing Function by Two Separate Mechanisms in Saccharomyces cerevisiae. Issue 2 (1st February 2017) - Kurdzo, Emily L; Obeso, David; Chuong, Hoa; Dawson, Dean S
Abstract: In meiosis I, chromosomes become paired with their homologous partners and then are pulled toward opposite poles of the spindle. In the budding yeast, Saccharomyces cerevisiae, in early meiotic prophase, centromeres are observed to associate in pairs in a homology-independent manner; a process called centromere coupling. Later, as homologous chromosomes align, their centromeres associate in a process called centromere pairing. The synaptonemal complex protein Zip1 is necessary for both types of centromere association. We aimed to test the role of centromere coupling in modulating recombination at centromeres, and to test whether the two types of centromere associations depend upon the same sets of genes. The zip1 -S75E mutation, which blocks centromere coupling but no other known functions of Zip1, was used to show that in the absence of centromere coupling, centromere-proximal recombination was unchanged. Further, this mutation did not diminish centromere pairing, demonstrating that these two processes have different genetic requirements. In addition, we tested other synaptonemal complex components, Ecm11 and Zip4, for their contributions to centromere pairing. ECM11 was dispensable for centromere pairing and segregation of achiasmate partner chromosomes; while ZIP4 was not required for centromere pairing during pachytene, but was required for proper segregation of achiasmate chromosomes. These findings help differentiate the two mechanisms that allow centromeres to interact in meiotic prophase, and illustrate that centromere pairing, which was previously shown to be necessary to ensure disjunction of achiasmate chromosomes, is not sufficient for ensuring their disjunction.